Cardio-oncological risk stratification and follow up: a new challenge for the general practitioner - Zemare, Mohamed Ali; Duchatelle, Valérie; Alexe, Raluca; Djokic, Bojan; Sierro, Christophe; Girod, Grégoire (Revue médicale suisse, 2023)
Rise of medical oncology, aging of populations and survival rates' improvement of patients suffering from cancer are all factors contributing to exponential rise of the exposure of patients to -cardiotoxic therapies. A multidisciplinary approach including a close cooperation between general practitioner and specialists will -promote an early identification and treatment of cardiovascular complications related to cancer treatments. This strategy has proven to have a truly positive impact on both cardiovascular and onco-logic prognosis. We will summarize throughout this article the last recommendations established by the European Society of Cardiology in terms of cardiovascular risk stratification and follow up planning through the use of clinical, biological and cardiac imaging data.